A Survey of Hybrid Routing Protocol for Interconnecting Mobile Ad Hoc Network and Internet - Ramesh, G; Geetha, M (International Journal of Computer Sciences and Engineering, 2018)
Mobile node is a collection of mobile nodes which forms a temporary network. Some of the nodes in an ad hoc network may want access to an external network, such as internet. Different mechanisms have been proposed to integrate MANETs and the Internet. These mechanisms are differing based on gateway discovery mechanism, and Adhoc routing protocol. When MANET is connected to the Internet, it is important for the mobile nodes to detect an available gateway providing an access to the Internet. The objective of this paper is a survey on the Mobile Ad-hoc Network (MANET) routing protocols used in gateways. This article presents a survey of hybrid solutions for integrating MANETs with the Internet.